2006 IEEE International Conference on Acoustics Speed and Signal Processing Proceedings
DOI: 10.1109/icassp.2006.1661491
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Multiresolution Techniques for Subcellular Protein Location Classification

Abstract: We propose an adaptive multiresolution (MR) approach for classification of fluorescence microscopy images of subcellular protein locations, providing biologically relevant information. These images have highly localized features both in space and frequency which naturally leads us to MR tools. Moreover, as the goal of the classification system is to distinguish between various protein classes, we aim for features adapted to individual proteins. These two requirements further lead us to adaptive MR tools. We st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…We now summarize our initial MR classification effort [12,13]. We started with a simple classification system consisting of Haralick texture feature computation followed by a maximum-likelihood classifier, and demonstrated that, by adding an MR block in front, we were able to raise the classification accuracy by roughly 10% (from 71.8% to 82.2%) as compared to the system with no MR.…”
Section: Introductionmentioning
confidence: 99%
“…We now summarize our initial MR classification effort [12,13]. We started with a simple classification system consisting of Haralick texture feature computation followed by a maximum-likelihood classifier, and demonstrated that, by adding an MR block in front, we were able to raise the classification accuracy by roughly 10% (from 71.8% to 82.2%) as compared to the system with no MR.…”
Section: Introductionmentioning
confidence: 99%
“…There is no reason why our approach in [8] would not work if we viewed each of the subbands as an individual classification branch and applied a generic classifier to it. This would enable us to come up with individual classification decisions at each particular subband.…”
Section: Proposed Algorithmmentioning
confidence: 95%
“…As we just discussed, although in [8] we demonstrated the power of adaptive MR techniques, problems still remain, mostly due to the classifier we used (maximum likelihood). The algorithm adjusts the weights trying to maximize the overall classification accuracy; however, the previous best is not kept.…”
Section: Proposed Algorithmmentioning
confidence: 95%
See 2 more Smart Citations